Genetically predicted lipids mediate the association between intrahepatic cholestasis of pregnancy and cardiovascular disease - Cui, Ji; Zhai, Qilong; Chen, Mengjie; Yang, Zhu (Frontiers in Cardiovascular Medicine, 2024)
Abstract：The influence of Intrahepatic cholestasis of pregnancy (ICP) on cardiovascular disease (CVD), including hypertension (HTN) and coronary artery disease (CAD), has not been thoroughly investigated. This study explores the causal relationship between ICP and CVD (HTN, CAD) using Mendelian Randomization (MR). Utilizing summary-level data from Genome-Wide Association Studies (GWAS), we applied the inverse-variance weighted (IVW) method, supplemented by sensitivity and reverse MR analyses, to ascertain robustness. Our findings reveal significant causal links, indicating ICP notably increases the risk of CVD (P=0.001), hypertension (HTN, P=0.024), and coronary artery disease (CAD, P=0.039). A two-step MR analysis highlighted the mediation role of lipid profiles, with LDL, TC, and Apo-B contributing to increased CVD risk by 25.5%, 12.2%, and 21.3%, respectively. Additionally, HTN was identified as a mediator in the ICP-CAD association, accounting for a 14.5% mediation effect. The results underscore the genetic predisposition of ICP to elevate CVD risk and the critical mediating role of lipid levels, emphasizing the need for vigilant lipid monitoring and early intervention in individuals with ICP.